Over-Expression of a Maize N-Acetylglutamate Kinase Gene (ZmNAGK) Improves Drought Tolerance in Tobacco - Liu, Weijuan; Xiang, Yang; Zhang, Xiaoyun; Han, Gaoqiang; Sun, Xiujuan; Sheng, Yu; Yan, Jingwei; Scheller, Henrik Vibe; Zhang, Aying (Frontiers in Plant Science, 2019)
Water deficit is a key limiting factor that affects the growth, development and productivity of crops. It is vital to understand the mechanisms by which plants respond to drought stress. Here an N-acetylglutamate kinase gene, ZmNAGK, was cloned from maize (Zea mays). ZmNAGK was expressed at high levels in maize leaves and at lower levels in root, stem, female flower and male flower. The expression of ZmNAGK was significantly induced by PEG, NaCl, ABA, brassinosteroid and H2O2. The ectopic expression of ZmNAGK in tobacco resulted in higher tolerance to drought compared to plants transformed with empty vector. Further physiological analysis revealed that overexpression of ZmNAGK could enhance the activities of antioxidant defense enzymes, and decrease malondialdehyde content and leakage of electrolyte in tobacco under drought stress. Moreover, the ZmNAGK transgenic tobacco accumulated more arginine and nitric oxide (NO) than control plants under drought stress. In addition, the ZmNAGK transgenic tobaccos activated drought responses faster than vector-transformed plants. These results indicate that ZmNAGK can play a vital role in enhancing drought tolerance by likely affecting the arginine and NO accumulation, and ZmNAGK could be involved in different strategies in response to drought stress.